An Analysis of Register of the Football Terms Used in online News of the BOLA Magazine - Tatik Juwita Ningsih; Suswanto Ismadi Megah; Nurul Aimi Razali (Universitas Riau Kepulauan, 2021)
This study deals with the register analysis of the Football terms used by journalist in the online media of “BOLA” news magazine. This study focused on the lexical and phrasal items of the grammatical features and contextual meaning of the register in the football terms. This study is deigned qualitatively. The findings show that there are 22 for lexical items, and 24 for phrasal items. Thus, in term of lexical mostly used by journalists in writing the terms of football lexically come to” team” and “youngster”. On the other hand, the mostly phrasal items found in the online media of BOLA news come to “Top scorer” with 6 occurrences (25%). The second places comes to “ Mid-week” with 3 occurrences (12.5%). This study can be concluded that the use of the lexical items of “youngster”, this register refers to the social context that football mostly played by young people. While in term of phrasal items come to the term of “Top scorer” to identify a player who has created or scores the most goals in a match. This term relates to the social context in term of the skill to kick the ball inside the goal keeper. On the other side, the use of the “Mid-week” is used to relate with the time of the match.Keywords: Register, Football terms, and Online News.